2019
DOI: 10.1103/physrevlett.122.151101
|View full text |Cite
|
Sign up to set email alerts
|

Echo Technique to Distinguish Flavors of Astrophysical Neutrinos

Abstract: The flavor composition of high-energy astrophysical neutrinos is a rich observable. However, present analyses cannot effectively distinguish particle showers induced by νe versus ντ . We show that this can be accomplished by measuring the intensities of the delayed, collective light emission from muon decays and neutron captures, which are, on average, greater for ντ than for νe. This new technique would significantly improve tests of the nature of astrophysical sources and of neutrino properties. We discuss t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 78 publications
(85 reference statements)
1
40
0
Order By: Relevance
“…The behavior with energy scales monotonically, as shown in the right-hand panel of Fig. 8, noting that the second and third peak are perfectly correlated (as also shown in [43]). We therefore use π + as a proxy for hadrons, and electrons for electromagnetic showers.…”
Section: Cherenkov Timing and Light Echossupporting
confidence: 59%
See 3 more Smart Citations
“…The behavior with energy scales monotonically, as shown in the right-hand panel of Fig. 8, noting that the second and third peak are perfectly correlated (as also shown in [43]). We therefore use π + as a proxy for hadrons, and electrons for electromagnetic showers.…”
Section: Cherenkov Timing and Light Echossupporting
confidence: 59%
“…Ref. [43] found that this leads to a distinctive three-peak signature in the time-evolution of the Cherenkov light produced by a high-energy neutrino. The first peak, which crests around 10 −7 s is the largest, and comes from the immediate energy deposition by primary particles.…”
Section: Cherenkov Timing and Light Echosmentioning
confidence: 99%
See 2 more Smart Citations
“…We briefly summarize the neutrino detection techniques used in IceCube and similar detectors [2,3,88,89]. Neutrinos interact with nuclei and electrons, producing relativistic particles that emit Cherenkov light that is detected by photomultiplier tubes.…”
Section: B Review Of Detection In Icecubementioning
confidence: 99%